A Population-Based Survey of the Workplace Costs for Caregivers of Persons With Treatment-Resistant Depression Compared With Other Health Conditions. Issue 9 (September 2020) - Lerner, Debra; Lavelle, Tara A.; Adler, David; Chow, Wing; Chang, Hong; Godar, Sean C.; Rogers, William H.
Abstract : Objective: To describe caregiving work outcomes and related indirect (ie, productivity) and direct (ie, caregiving hours and expenses) costs. Methods: A national, population-based survey to identify employed caregivers assisting a person with treatment-resistant depression (TRD) and a comparison group of employed caregivers assisting others (No TRD). Results: Screening identified 169 TRD caregivers and 1070 No TRD caregivers providing 23.3 and 14.6 mean weekly caregiving hours, respectively. Adjusted annual indirect cost estimates were 11, 121 for caregivers of TRD and 7761 for caregivers in the No TRD group ( P ⩽ 0.0001). At-work productivity loss (presenteeism) was the largest component. Adjusted annual direct cost estimates were 29, 805 for caregivers of TRD and 20, 642 for caregivers in the No TRD group ( P ⩽ 0.0001). Conclusions: TRD exacts a toll on caregivers and their employers exceeding that for other caregivers. Abstract : Supplemental Digital Content is available in the text